The association of post-discharge adverse events with timely follow-up visits after hospital discharge. - Dennis Tsilimingras; Samiran Ghosh; Ashley Duke; Liying Zhang; Henry Carretta; Jeffrey Schnipper (PLoS ONE, 2017)
There has been little research to examine the association of post-discharge adverse events (AEs) with timely follow-up visits after hospital discharge. We aimed to examine whether having a timely follow-up outpatient visit would reduce the risk for post-discharge AEs.This was a methods study of patients at risk for post-discharge AEs from December 2011 through October 2012. Five hundred and forty-five patients who were under the care of hospitalist physicians and were discharged home from a community hospital, spoke English, and could be contacted after discharge were evaluated. The aim of the study was to examine the association of post-discharge AEs with timely follow-up visits after hospital discharge based on structured telephone interviews, health record review, and adjudication by two blinded, trained physicians using a previously established methodology.We observed a higher incidence of AEs with patients that had their first follow-up visit within 7 days after hospital discharge (33.5% vs. 23.0%, p = 0.007). This effect was attenuated somewhat but remained significant when adjusted for several patient factors (adjusted OR 1.33, 95% confidence interval 1.16-2.71).This observational study paradoxically showed an increase in post-discharge AEs with early follow-up, likely a result of confounding by indication and/or information bias that could not be completely adjusted for. This study illustrates the potential hazards with conducting observational studies to determine the efficacy of various transitional care interventions, such as early follow-up, where risk for confounding by indication is high.